Dunia Cyber, Sarana Kekuasaan dan Produksi Pengetahuan Baru - Moses, Robertus (Perspektif, 2019)
The theme of power is always relevant for our discussion. Understanding the face of power, however, tends to change from time to time. In this modern age, with the development of technological devices, power has undergone a shift of understanding as well. Power is not only in the real world, but also runs in the cyber world by certain parties. Manipulation of power, as initiated by Michel Foucault, is increasingly prevalent in the cyber world. Through the cyber world, the governmental institutions in power are increasingly sophisticated. Power is increasingly difficult to identify the shape and face. Who is the master of technology, he is the one who has the power, he is the new ruler. The manipulation of the truth of knowledge produced by the rulers is also the more we receive. The rulers are regarded as the true source of knowledge, although knowledge is a lie or a manipulation. The writer argues, in order to build a good power, it takes the spirit to escape from instant culture and to foster an integral spirit in the social media that includes the environment, social and spiritual realm.